Legal Challenges in Regulating Cryptocurrency: A Comparative Analysis - Siti laelatul rodiah; Sandra Yuli Trisnawati (Green Social: International Journal of Law and Civil Affairs, 2024)
Cryptocurrency has emerged as a disruptive force in the financial sector, presenting new regulatory challenges. This article investigates the current legal landscape surrounding cryptocurrency, addressing issues such as tax compliance, fraud prevention, and investor protection. Through a comparative study, the paper evaluates different regulatory approaches and their effectiveness in achieving financial stability while fostering innovation. The findings offer insights into the balance required between regulation and the growth of digital currencies.